Pengelolaan Stok Obat-Obatan Dalam Meningkatkan Pelayanan Di Puskesmas Terjun Kecamatan Medan Marelan - Buyung Solihin Hasugian; Zulham; Aulia Rahmah, Sabrina (Unity Academy, 2023)
Service in the provision of treatment is one of the compatibility that cannot be separated from the implementation of health efforts that play an important role in improving the quality of health services in the community. Poor drug storage can interfere with efforts to improve the quality of drugs at the puskesmas. Plumbing Health Center is one of the health centers located in Medan City, precisely in Medan Marelan District. With its strategic location, it is not uncommon for this puskesmas to be visited by the local community as a referral material for treatment. The system used to check drug stocks is still manual, namely by writing and checking one by one the empty and existing drug stocks. This makes the work of the health workers or pharmacists who work slow because they have to check the stock of medicines needed by the community. The application that will be built later is an application that can be used by pharmacists to help ease their work, especially in the checking of existing drug stocks. The activity plan that will be proposed is to carry out socialization activities as well as training for health workers at the puskesmas to engage in using the application that was built, to help ease work.